Highly efficient exciplex-emission from spiro[fluorene-9, 9′-xanthene] derivatives. (February 2021) - Cao, Hong-Tao; Wan, Jun; Li, Bo; Zhang, He; Xie, Ling-Hai; Sun, Chen; Feng, Quan-You; Yu, Wen-Jing; Huang, Wei
Abstract: Exciplex-thermally activated delayed fluorescence (TADF) is significant due to its potential in energy-saving and flexible techniques, but still suffers from complicated-synthesis materials and low-efficiency devices. Herein, we synthesize two new spiro[fluorene-9, 9′-xanthene] (SFX)-based acceptors, 2-(4, 6-diphenyl-1, 3, 5-triazin-2-yl)-SFX (TRZSFX) and 2, 7-bis(4, 6-diphenyl-1, 3, 5-triazin-2-yl)-SFX (DTRZSFX) via convenient method, and obtain exciplex-emitters using the tris(4-carbazoyl-9-ylphenyl)amine (TCTA) as a donor. The results suggest that two devices based on TCTA:TRZSFX and TCTA:DTRZSFX display excellent exciplex-TADF accompanied by appealing efficiencies of 79.6 cd A −1 and 78.1 lm W −1 . Encouragingly, a maximum value of 22.5% in external quantum efficiency (EQE) is realized for TCTA:TRZSFX-based device, which is higher than those of most reported exciplex OLEDs as far as we know. Our work offers a promising avenue for developing high-efficiency exciplex-emissions. Graphical abstract: Image 1 Two novel triazine-substituted spiro[fluorene-9, 9′-xanthene] derivatives are prepared as electron acceptors to form high-performance exciplex-emissions with excellent efficiencies of 79.6 cd A −1, 78.1 lm W −1 and 22.5%. Highlights: Two triazine-substituted SFX derivatives were synthesized as electron acceptors. The triazine-substituted acceptors possess exciplex-TADF feature. The TCTA:TRZSFX film exhibits photoluminescence efficiency of 73%. The TCTA:TRZSFX-based device displays external quantum efficiency of 22.5%. The excellent emission efficiencies benefit from the triazine-substitution in SFX.